Analytical subthreshold swing model of junctionless elliptic gate-all-around (GAA) FET - Hakkee Jung (AIMS Electronics and Electrical Engineering)
An analytical subthreshold swing (SS) model has been presented to determine the SS of an elliptic junctionless gate-all-around field-effect transistor (GAA FET). The analysis of a GAA FET with an elliptic cross-section is essential because it is difficult to manufacture a GAA FET with an accurate circular cross-section during the process. The SS values obtained using the proposed SS model were compared with 2D simulation values and other papers to confirm good agreement. Using this analytical SS model, SS was analyzed according to the eccentricity of the elliptic cross-section structure. As a result, it was found that the carrier control ability within the channel improved as the eccentricity increased due to a decrease in the effective channel radius by a decrease in the minor axis length and a decrease in the minimum potential distribution within the channel, and thus the SS decreased. There was no significant change in SS until the eccentricity increased to 0.75 corresponding to the aspect ratio (AR), the ratio of the minor and major axis lengths, of 1.5. However, SS significantly decreased when the eccentricity increased to 0.87 corresponding to AR = 2. As a result of the SS analysis for changes in the device parameters of the GAA FET, changes in the channel length, radius, and oxide film thickness significantly affected the changing rate of SS with eccentricity.